General geology and petrography of igneous & metamorphic rocks at Bandar Jeli, Kelantan - Muhammad Ijaz Hassan (2013)
The study area is located at Bandar Jeli in the district of Jeli, Kelantan. Geological mapping and petrographic analysis are the main methods used in the study. The objectives of the study are to produce detailed geological map as well as identifying minerals and texture present in the thin section of the samples collected. Based on the geological mapping and petrographic analysis, majority of the area is made up of biotite granite porphyry. It has porphyritic texture and its age can be correlated with Kemahang Granite and considered to have Triassic age. The main minerals present in biotite granite porphyry are plagioclase feldspar (70%), biotite (15%), quartz(10%), microcline (3%) and hornblende(7%). Present of metamorphic rocks in the fields are actually biotite granite porphyry protolith. These minerals have undergone alignment or foliation that leads it to the classification of metamorphic rocks. Gneiss are resulted when the biotite granite porphyry are subjected to high pressure and temperature at the area. Mylonite is formed due to the presents of shear fault at the area. However, these metamorphic rocks are not mapable as it only presents at small area with limited availability of outcrop.